Analisis Bibliometrik: Trend Penelitian Kemampuan Literasi Numerasi Dan Literasi Digital Dalam Pembelajaran Matematika - Rohmah, Siti Nur; Hidayat, Rifqi; Rohaeti, Titi (ANARGYA: Jurnal Ilmiah Pendidikan Matematika, 2024)
The results showed that Indonesia students had an average math score less than the average score from the OECD. This is due to the fact that TIMMS and PISA materials consist of questions related to real-world problems. According to the results of Indonesia's digital literacy index organized by the Ministry of Communication and Information Technology (Kemkominfo) and the Katadata Insight Center (KIC) in 2021, Indonesia's digital literacy index is in the medium category, the level of digital literacy in Indonesia can still be categorized as low. The purpose of this study is to find out how the trend of numeracy literacy and digital literacy research with articular storyline 3. This method of research USES experimental or experimental research. The study is done to get an overall picture of numeration literacy and digital literacy. The goal was achieved by performing a bibliometric analysis. The findings of the study analyzed from 309 primary studies between 2019-2024 show trand numerating literacy and digital literacy of using the web-based learning media that articulated storyline 3. The results of bibliometrics based on terms and themes regarding numeracy literacy and digital literacy have a dim color so that in the study there are still few who conduct research, especially on triangular and quadrilateral matter. Therefore, this can be a reference for newness or novelty in future research